Gatewatching and news curation journalism, social media, and the public sphere - Bruns, Axel 1970- (New York Peter Lang, 2018)
Gatewatching and News Curation: Journalism, Social Media, and the Public Sphere documents an emerging news media environment that is characterised by a more and more networked and social structure.
Includes bibliographical references (pages 373-376) and index.
Keywords: Online journalism; Blogs; Journalism -- Objectivity